Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1074/jbc.271.14.8365
|View full text |Cite
|
Sign up to set email alerts
|

A Nuclear Envelope-associated Kinase Phosphorylates Arginine-Serine Motifs and Modulates Interactions between the Lamin B Receptor and Other Nuclear Proteins

Abstract: Previous studies have identified a subassembly of nuclear envelope proteins, termed "the LBR complex." This complex includes the lamin B receptor protein (LBR or p58), a kinase which phosphorylates LBR in a constitutive fashion (LBR kinase), the nuclear lamins A and B, an 18-kDa polypeptide (p18), and a 34-kDa protein (p34/p32). The latter polypeptide has been shown to interact with the HIV-1 proteins Rev and Tat and with the splicing factor 2 (SF2). Using recombinant proteins produced in bacteria and syntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
110
1
29

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(142 citation statements)
references
References 43 publications
2
110
1
29
Order By: Relevance
“…The positions of the 1000-and 300-bp markers are indicated. F, detection of Lys 14 -acetylated and Lys 9 -trimethylated histone H3 in LBR-precipitated chromatin, as documented by Western blotting. Equal proportions of the nonbound (lanes 1) and the LBR-bound (lanes 2) material are shown.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The positions of the 1000-and 300-bp markers are indicated. F, detection of Lys 14 -acetylated and Lys 9 -trimethylated histone H3 in LBR-precipitated chromatin, as documented by Western blotting. Equal proportions of the nonbound (lanes 1) and the LBR-bound (lanes 2) material are shown.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, another peak at 985.5 could be attributed either to a twice trimethylated or to a trimethylated/ acetylated peptide. Pull-down assays with recombinant LBR and Western blotting with anti-histone modification antibodies showed that H3 subspecies trimethylated at Lys 9 or acetylated Lys 14 were present in the LBR precipitate, albeit to a different extent (Fig. 2F).…”
Section: Lbr Associates With Peripheralmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmids, Expression of Proteins, and Antibodies-Human SRPK1, the wild-type NH 2 -terminal domain of LBR (GST-wtNt; amino acids 1-205), and a mutant form lacking the RS motifs (GST-⌬RS; lacks amino acids [75][76][77][78][79][80][81][82][83][84] 75 RSRSRSRSRS 84 ) were expressed as fusion proteins with GST using the pGEX-2T vector (Amersham Biosciences) (18,19). Fulllength SRPK1 was also subcloned into the p-FLAG-CMV-2 (Eastman Kodak) vector and expressed in 293T cells with a FLAG tag fused at its NH 2 terminus (20).…”
Section: Methodsmentioning
confidence: 99%
“…A number of mammalian kinases have been shown to cause disassembly of nuclear speckles and relocalization of splicing factors, and to subsequently affect splicing factor activity. SRPK-1/2, Clk-1/2/3/4, cdc2-kinase, cyclin Ecdk2, topoisomerase I, U1 70-kDa associated kinase, cGMPdependent kinase, and lamin B-receptor kinase were all shown to phosphorylate SR proteins and other splicing factors in vitro (Woppmann et al, 1993;Gui et al, 1994;Colwill et al, 1996;Nikolakaki et al, 1996;Rossi et al, 1996;Nayler et al, 1997;Duncan et al, 1998;Kuroyanagi et al, 1998;Okamoto et al, 1998;Seghezzi et al, 1998;Wang et al, 1998;Koizumi et al, 1999;Wang et al, 1999). In addition, some of these kinases were shown to affect the splicing activity of such factors (Mermoud et al, 1994;Cao et al, 1997;Xiao and Manley, 1998;Prasad et al, 1999).…”
mentioning
confidence: 99%